THE EFFECT OF SOCIAL MEDIA PROMOTION AND PRICING ON PURCHASE DECISION AT CAFE SEARAH MALANG - Nely Sahida; Sudiono Putri, Kartika Anggraeni (Universitas Islam Lamongan, 2023)
This study aims to determine the effect of social media promotion and pricing on purchasing decisions at Cafe Searah Malang. The research method used in this study is a quantitative research method. The sample used was 125 respondents (25 question items x5) referring to the Malhotra theory and the sample in this study were students in Malang. The test was carried out using the statistical package for the social sciences (SPSS). The sampling technique in this study used a purposive sampling technique. The results of this study indicate that the effect of social media promotion and pricing partially and simultaneously has a significant effect on purchasing decisions.